Resveratrol: A potential therapeutic natural polyphenol for neurodegenerative diseases associated with mitochondrial dysfunction - Yadav, Ekta; Yadav, Pankajkumar; Khan, Mohd Masih Uzzaman; Singh, HariOm; Verma, Amita (Frontiers in Pharmacology, 2022)
Most polyphenols can cross blood-brain barrier, therefore, they are widely utilized in the treatment of various neurodegenerative diseases (ND). Resveratrol, a natural polyphenol contained in blueberry, grapes, mulberry, etc., is well documented to exhibit potent neuroprotective activity against different ND by mitochondria modulation approach. Mitochondrial function impairment is the most common etiology and pathological process in various neurodegenerative disorders, viz. Alzheimer's disease, Parkinson's disease, Huntington's disease and amyotrophic lateral sclerosis. Nowadays these ND associated with mitochondrial dysfunction have become a major threat to public health as well as health care systems in terms of financial burden. Currently available therapies for ND are limited to symptomatic cures and have inevitable toxic effects. Therefore, there is a strict requirement for a safe and highly effective drug treatment developed from natural compounds. The current review provides updated information about the potential of resveratrol to target mitochondria in the treatment of ND.